PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING DAN PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK SEKOLAH DASAR - Irvanda Julian Awal; Dayu Rika Perdana; Handoko; Muhammad Nurwahidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was the low learning motivation of fourth-grade students at SD Negeri 6 Metro Timur. This study aimed to determine the effect of the contextual teaching and learning model and problem-based learning on student learning motivation in Pancasila Education. The method used was quantitative with a quasi-experimental design. The population included all fourth-grade students in classes A and B, and the sample was determined using purposive sampling. Data collection techniques were conducted through tests and non-tests. The data were analysed using simple linear regression and the Independent Sample T-test. The results showed that the contextual teaching and learning model had an effect on student motivation to learn with a significance value of 0.018 < 0.05. there was an effect of the problem-based learning model with a significance value of 0.016 < 0.05, and there was a difference in the effect between the application of the contextual teaching and learning model and the problem-based learning model on student learning motivation with a significance value of 0.002 < 0.05.